f − 1 = f ′
The inverse of function f is equal to its first derivative as shown above. If f ( 2 ) = 2 , what is the value of f ′ ′ ( 2 ) ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
The derivative of an inverse function can be formulated as: [ f − 1 ]' × [f'( f − 1 )] = 1.
Since f − 1 = f', then f'' × f − 1 ( f − 1 ) = 1.
f(2) = 2 = f − 1 (2).
Substitute the value of 2 for f − 1 ,
f''(2)× f − 1 ( f − 1 (2)) = 1.
f''(2)×2 = 1; f"(2) = 0.5
Is there a function that satisfies this condition?
Log in to reply
I think so. The simplest form of polynomial f would have a degree of a golden ratio though I haven't found which would have f(2) = 2. (I caught a cold lately.) :(
A function which satisfies this condition could have the form A*x^B where B is the golden ratio (phi) and A = 2^(1-phi).
By inverse function theorem: f − 1 ( x ) = f ′ ( x ) → f ′ ( f − 1 ( x ) ) 1 = f ′ ′ ( x ) → f ′ ( f ′ ( x ) ) 1 = f ′ ′ ( x ) Also we are given that f ( 2 ) = 2 → f − 1 ( 2 ) = 2 → f ′ ( 2 ) = 2 → f ′ ′ ( 2 ) = f ′ ( f ′ ( 2 ) ) 1 = f ′ ( 2 ) 1 = 0 . 5
Problem Loading...
Note Loading...
Set Loading...
Because f ′ = f − 1 we can get f ′ ( f ( x ) ) = f − 1 ( f ( x ) ) = x
so f ′ ( f ( x ) ) = x so we can get f ′ ( f ( 2 ) ) = 2 or f ′ ( 2 ) = 2
we derivate each side so we can get
f " ( f ( x ) ) f ′ ( x ) = 1 substitute the value of 2 we can get
f " ( f ( 2 ) f ′ ( 2 ) ) = 1 ⇔ f " ( 2 ) = f ′ ( 2 ) 1 = 2 1 = 0 . 5